Design of Packaging Materials Based on Polylactide and Wood Filler - R. Safin, R.; A. Talipova, G.; R. Galyavetdinov, N. (International Journal of Engineering and Technology, 2018)
Packaging is one of the primary factors that influence the consumerâ€™s decision to purchase a product. Competent packaging design makes it possible to distinguish the product from competitorsâ€™ products, to attract the attention of the target audience, to raise the mood of the buyer,and to cause trust in the brand. Currently, packaging materials from various types of polymers are a popular and widely used type of packaging, but at the same time such materials pose a serious burden on the environment. In this regard, the development of new types of biodegradable materials for the packaging industry is relevant. The article considers the possibility of using a composite material for packing based on polylactide (PLA) and filler from crushed biomass waste. It was established that PLA packaging with the addition of 50% wood filler will provide high strength characteristics with the ability to create container packaging, as well as provide a high rate of biodegradation of used packaging, thereby reducing the environmental burden on the environment. At the same time, the cost of such a composite will be comparable to the cost of synthetic polymers obtained from non-renewable hydrocarbon raw materials.Â Â